Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Sure! Let's go through the steps to factorize the given polynomials using the concept of perfect squares.
### (a) [tex]\( x^4 + 6x^2 + 9 \)[/tex]
1. Identify the form [tex]\( a^2 + 2ab + b^2 = (a + b)^2 \)[/tex].
2. Let's set [tex]\( a = x^2 \)[/tex] and [tex]\( b = 3 \)[/tex].
3. Substitute these values to rewrite the polynomial:
[tex]\[ (x^2)^2 + 2 \cdot x^2 \cdot 3 + 3^2 = (x^2 + 3)^2 \][/tex]
Therefore, the factorized form is:
[tex]\[ \boxed{(x^2 + 3)^2} \][/tex]
### (b) [tex]\( 9x^4 - 12x^2 + 4 \)[/tex]
1. Identify the form [tex]\( a^2 - 2ab + b^2 = (a - b)^2 \)[/tex].
2. Let's set [tex]\( a = 3x^2 \)[/tex] and [tex]\( b = 2 \)[/tex].
3. Substitute these values to rewrite the polynomial:
[tex]\[ (3x^2)^2 - 2 \cdot 3x^2 \cdot 2 + 2^2 = (3x^2 - 2)^2 \][/tex]
Therefore, the factorized form is:
[tex]\[ \boxed{(3x^2 - 2)^2} \][/tex]
### (c) [tex]\( 25x^6 - 60x^3 + 36 \)[/tex]
1. Identify the form [tex]\( a^2 - 2ab + b^2 = (a - b)^2 \)[/tex] (Note that the middle term needs simplification).
2. Let's set [tex]\( a = 5x^3 \)[/tex] and [tex]\( b = 3 \)[/tex].
3. Substitute these values to rewrite the polynomial:
[tex]\[ (5x^3)^2 - 2 \cdot 5x^3 \cdot 3 + 3^2 = (5x^3 - 3)^2 \][/tex]
Therefore, the factorized form verifies to be:
[tex]\[ \boxed{(5x^3 - 3)^2} \][/tex]
Each polynomial is transformed into a perfect square, which completes their factorization.
### (a) [tex]\( x^4 + 6x^2 + 9 \)[/tex]
1. Identify the form [tex]\( a^2 + 2ab + b^2 = (a + b)^2 \)[/tex].
2. Let's set [tex]\( a = x^2 \)[/tex] and [tex]\( b = 3 \)[/tex].
3. Substitute these values to rewrite the polynomial:
[tex]\[ (x^2)^2 + 2 \cdot x^2 \cdot 3 + 3^2 = (x^2 + 3)^2 \][/tex]
Therefore, the factorized form is:
[tex]\[ \boxed{(x^2 + 3)^2} \][/tex]
### (b) [tex]\( 9x^4 - 12x^2 + 4 \)[/tex]
1. Identify the form [tex]\( a^2 - 2ab + b^2 = (a - b)^2 \)[/tex].
2. Let's set [tex]\( a = 3x^2 \)[/tex] and [tex]\( b = 2 \)[/tex].
3. Substitute these values to rewrite the polynomial:
[tex]\[ (3x^2)^2 - 2 \cdot 3x^2 \cdot 2 + 2^2 = (3x^2 - 2)^2 \][/tex]
Therefore, the factorized form is:
[tex]\[ \boxed{(3x^2 - 2)^2} \][/tex]
### (c) [tex]\( 25x^6 - 60x^3 + 36 \)[/tex]
1. Identify the form [tex]\( a^2 - 2ab + b^2 = (a - b)^2 \)[/tex] (Note that the middle term needs simplification).
2. Let's set [tex]\( a = 5x^3 \)[/tex] and [tex]\( b = 3 \)[/tex].
3. Substitute these values to rewrite the polynomial:
[tex]\[ (5x^3)^2 - 2 \cdot 5x^3 \cdot 3 + 3^2 = (5x^3 - 3)^2 \][/tex]
Therefore, the factorized form verifies to be:
[tex]\[ \boxed{(5x^3 - 3)^2} \][/tex]
Each polynomial is transformed into a perfect square, which completes their factorization.
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.